ANALYSIS OF GO JEK E-SERVICE QUALITY AND ITS EFFECT ON CUSTOMER SATISFACTION IN JAMBI CITY - Novita Sari; Yenny Yuniarti (Management Department, Faculty of Economics and Business, Universitas Jambi, 2018)
The development of technology is one of the supporting tools for companies capable of meeting the needs of consumers, by providing the best service. One technology-based business is GO Jek. GO jek is a company that leads the ojek transportation industry revolution that was pioneered since 2010. The technology-based Go Jek service or known as the quality of electronic services (E-service) provides convenience to customers through internet media. The research method is descriptive verification with multiple linear regression analysis tools. The number of samples used was 164 respondents. The results showed the simultaneous effect of variable e-service quality on consumer satisfaction of Go Jek in Jambi City. The dominant sub-variable influencing is an efficiency that is equal to 50.66%.